Biomarkers for Tuberculosis Based on Secreted, Species-Specific, Bacterial Small Molecules. (26th May 2015) - Pan, Shih-Jung; Tapley, Asa; Adamson, John; Little, Tessa; Urbanowski, Michael; Cohen, Keira; Pym, Alexander; Almeida, Deepak; Dorasamy, Afton; Layre, Emilie; Young, David C.; Singh, Ravesh; et al.
Abstract : Improved biomarkers are needed for tuberculosis. To develop tests based on products secreted by tubercle bacilli that are strictly associated with viability, we evaluated 3 bacterial-derived, species-specific, small molecules as biomarkers: 2 mycobactin siderophores and tuberculosinyladenosine. Using liquid chromatography–tandem mass spectrometry, we demonstrated the presence of 1 or both mycobactins and/or tuberculosinyladenosine in serum and whole lung tissues from infected mice and sputum, cerebrospinal fluid (CSF), or lymph nodes from infected patients but not uninfected controls. Detection of the target molecules distinguished host infection status in 100% of mice with both serum and lung as the target sample. In human subjects, we evaluated detection of the bacterial small molecules (BSMs) in multiple body compartments in 3 patient cohorts corresponding to different forms of tuberculosis. We detected at least 1 of the 3 molecules in 90%, 71%, and 40% of tuberculosis patients' sputum, CSF, and lymph node samples, respectively. In paucibacillary forms of human tuberculosis, which are difficult to diagnose even with culture, detection of 1 or more BSM was rapid and compared favorably to polymerase chain reaction–based detection. Secreted BSMs, detectable in serum, warrant further investigation as a means for diagnosis and therapeutic monitoring in patients with tuberculosis.